예비 특수교사에게 필요한 디지털 역량에 대한 특수교사의 인식 - 박희정(Heejung Park); 강혜진(Hyejin Kang); 장지현(Jihyun Jang) (언어치료연구, 2023)
목적: 본 연구는 예비 특수교사가 갖추어야 할 디지털 역량에 대한 특수교사의 인식을 조사함으로써, 특수교사 양성을 위해 교육과정에 포함되어야 할 디지털 역량을 알아보고자 하는 데 목적이 있다. 방법: Kang 등(2023)의 연구를 통해 도출된 특수교사에게 요구되는 디지털 역량(테크놀로지 활용, AI 융합교육, 생산 및 공유, 정보 활용, 컴퓨팅 사고, 디지털 윤리, 협업 및 의사소통)을 기반으로 하여 특수교사 80명을 대상으로 온라인 시스템을 활용하여 장애학생 미래교육을 위해 예비 특수교사가 갖추어야 할 디지털 역량에 대한 인식을 조사하였다. 결과: 첫째, 장애학생 미래교육을 위해 특수교사가 갖추어야 할 디지털 역량의 중요도와 필요성을 특수교사를 대상으로 조사한 결과 디지털 역량 교육의 중요도에 대해서 86.25%가 ‘그렇다’ 이상으로 긍정적으로 인식하였으며, 디지털 역량 교육의 필요성에 대해서도 85.00%가 ‘그렇다’ 이상으로 긍정적으로 인식하였다. 둘째, 디지털 역량별 중요도 및 필요성, 선호도를 분석한 결과 정보 활용 역량이 가장 높게 나타났다. 디지털 역량별 하위능력을 분석한 결과, 디지털 윤리 역량은 ‘저작권에 대한 이해 능력’, 생산 및 공유 역량은 ‘수업 영상 자료 제작 능력’, 테크놀로지 활용 역량은 ‘디지털 기기 조작 능력’, 정보 활용 역량은 ‘수업 자료 활용 능력’, 컴퓨팅 사고 역량은 ‘교육과정과 알고리즘 연계 능력’, AI(인공지능) 융합교육 역량은 ‘인공지능 수업 활용 능력’, 협업 및 의사소통 역량은 ‘문서도구 및 프로그램 활용’과 ‘학생대상 교육을 제공하기 위한 능력’이 각 역량에서 선호도가 가장 높게 나타났다. 결론: 미래교육 대응 교사의 역량을 강화하기 위해서 특수교사 양성을 위한 교육과정에 디지털 역량 교육이 포함되어야 할 것이다. Purpose: This study aims to explore the digital competencies that should be included in the education curriculum for pre-service special education teachers by investigating the perceptions of special education teachers regarding the essential digital competencies. Methods: Building upon the digital competencies identified in the study by Kang et al. (2023) which encompass technology utilization, AI-convergence education, production and sharing, information utilization, computational thinking, digital ethics, collaboration and communication--an online survey was conducted with 80 special education teachers. The survey aimed to assess the awareness of digital competencies required for pre-service special education teachers to facilitate future education for students with disabilities. Results: First, when surveyed about the importance and necessity of digital competencies for future education of students with disabilities, 86.25% of the special education teachers responded positively with ‘agree’ or higher regarding the importance of digital competency education, and 85% responded positively with ‘agree’ or higher regarding the necessity of such education. Second, an analysis of importance, necessity, and preferences of digital competencies revealed that information utilization competency scored the highest. Among the sub-abilities of each competency, digital ethics competency demonstrated ‘understanding of copyright’, production and sharing competency involved ‘ability to create instructional video materials’, technology competency required ‘digital device operation skills’, information utilization competency encompassed ‘ability to utilize teaching materials’, computational thinking competency exhibited ‘integration of curriculum and algorithms’, AI-convergence education competency encompassed ‘utilization of AI in lessons’, and collaboration and communication competency encompassed ‘proficiency in document tools and programs’, and ‘ability to provide student-targeted education’. Conclusions: To enhance the readiness of educators for future education, it is imperative to incorporate digital competency education into the curriculum for pre-service special education teachers. KCI Citation Count: 0